A new vision of the Adriatic Dense Water future under extreme warming - C. Denamiel; C. Denamiel; I. Tojčić; I. Tojčić; P. Pranić (Ocean Science, 2025)
We use the Adriatic Sea and Coast (AdriSC) kilometer-scale atmosphere–ocean model to assess the impact of a far-future extreme-warming scenario on the formation, spreading, and accumulation of North Adriatic Dense Water (NAddW) over the entire basin, including the Jabuka Pit accumulation site, and Adriatic Deep Water (AdDW) over the Southern Adriatic Pit (SAP). Our key findings differ from previous studies that used coarser Mediterranean climate models and did not update the thresholds for dense-water and deep-water definitions to account for the far-future background density changes caused by warmer sea surface temperatures. We show that surface buoyancy losses at NAddW generation sites, driven by evaporation, are expected to increase by 15 % under extreme warming, despite a 25 % reduction in the intensity and spatial extent of Bora winds. As a result, future NAddW formation will remain similar to present conditions. However, the volume of dense water in the Jabuka Pit will decrease due to the increased far-future stratification. Additionally, dense-water transport between the Jabuka Pit and the deepest part of the SAP will stop, as future NAddW will be lighter than the AdDW. Regarding Ionian–Adriatic exchanges, extreme warming will not affect the impact of the bimodal oscillation system on the Adriatic salinity variability, but future AdDW dynamics will be determined by density changes in the northern Ionian Sea. Our findings highlight the complexity of climate change impacts on Adriatic atmosphere–ocean processes and the importance of high-resolution models for more accurate far-future projections in the Adriatic Sea.